3-D abstract sculpture as an artistic endeavour toward innovative landscape architectural design / Masbiha Mat Isa, Muhammad Hafiz Zainal and Noor Syarafina Mohd Fauzi - Mat Isa, Masbiha; Zainal, Muhammad Hafiz; Mohd Fauzi, Noor Syarafina (2023)
Art allows people to express their uniqueness and stimulate reflection on the world around them. In the landscape of the professional field, there is a large amount of different knowledge that must be mastered by the students before graduating as a landscape architect (Karl B. Lohmann, B.S., 1963). One of the fundamental knowledge that needs to be learned is related to the combination of artistic intuition and creativity to produce quality graphic expression in design with systematic scientific analytical thinking (Gazvoda, 2002). Incorporating artistic practices into the landscape design process will increase overall knowledge generation, leading to better results.